PENGARUH FIRM CHARACTERISTICS, AUDIT QUALITY, DAN FREE CASH FLOWS TERHADAP EARNINGS MANAGEMENT - Enrico Sutopo; Muhammad Arief Effendi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence regarding the effect of firm characteristics, audit quality, and free cash flow as independent variables on earnings management as the dependent variable. The dependent variable of earning management is measured by using the Modified Jones Model. The population used is non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. There are 193 non-financial companies used as samples in this study which were taken using the purposive sampling method. This research uses multiple regression analysis to analyze the data used. The results of this study indicate that financial performance and free cash flow have no effect on earnings management. Meanwhile, firm size, leverage, board of directors, audit committee size, independent commissioners, audit quality, and firm age affect earnings management